Detection of bacterial contaminants via frequency manipulation of amino-groups functionalized Fe3O4 nanoparticles based resonant sensor. (1st November 2022) - Kale, Vivek; Chavan, Chetan; Bhapkar, Sunil; Girija, K G; Kale, S N
Abstract: Bacterial infections have a large impact on public health. Through this study, we report on the development of complementary split-ring resonators (CSRR) supplemented by functionalized nanoparticles to detect bacteria in the aqueous medium. Iron oxide (Fe3 O4 ) nanoparticles were functionalized with amino groups using (3-aminopropyl) triethoxysilane (APTES) to form (APTES@Fe3 O4 ) nanoparticles, which have a specific affinity towards the bacterial species. This affinity was evaluated using the Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) bacterial species. The resonant sensor was tuned at 430 MHz and the CSRR sensor bed was further activated using APTES@Fe3 O4 nanoparticles. Bacterial detection was studied over a range of concentrations from 2.66 × 10 9 cells to 2.66 × 10 8 cells. The sensor actively responded to small changes in bacterial concentration, showing an overall shift in resonance frequency of ∼44 MHz (∼40 MHz/cell count) for E. coli and ∼55 MHz (50.43 MHz/cell count) for S. aureus . Dextran sulphate and Chitosan were used as the references. The magnetic character of the conjugated system exhibited strong interaction of the bacterial species with APTES@Fe3 O4, justifying the high selectivity towards these species. This demonstrates the feasibility of a sensitive, fast, portable device, against the traditionally used time-consuming bio-assays.